2003
DOI: 10.1093/pubmed/fdg030
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness of community pharmacy-based interventions to reduce risk behaviours and risk factors for coronary heart disease

Abstract: The peer-reviewed literature demonstrates the contribution of community pharmacy-based services to the reduction of risk behaviours and risk factors for CHD. The evidence supports the wider provision of smoking cessation and lipid management through community pharmacies. Health commissioners and planners can use the findings of this review to incorporate community pharmacy based health development activities into local health services. Further research is needed into the contribution of community pharmacy to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 17 publications
3
92
1
2
Order By: Relevance
“…The aforementioned Iranian study showed that although two-third of the participants believed that well-trained pharmacists can effectively deliver such services in community pharmacies, cholesterol screening services were rarely provided in Iranian community pharmacies. In contrast to these findings, pharmacists in developed countries have been involved in cholesterol screening and cardiovascular risk assessment for decades (Blenkinsopp et al, 2003;Bluml et al, 2000). That …”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned Iranian study showed that although two-third of the participants believed that well-trained pharmacists can effectively deliver such services in community pharmacies, cholesterol screening services were rarely provided in Iranian community pharmacies. In contrast to these findings, pharmacists in developed countries have been involved in cholesterol screening and cardiovascular risk assessment for decades (Blenkinsopp et al, 2003;Bluml et al, 2000). That …”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists routinely provide drug use advice and compatibility checks within drug regimens, but they are also able to supply patient education and basic clinical monitoring for several chronic conditions [1,2]. As drug specialists, they can optimise drug safety and efficiency and contain drug costs by analysing drug regimens and detecting adherence issues [3][4][5][6][7][8][9][10]. Therefore, a pharmaceutical service termed Medication Review (MR) service has been implemented in several countries [11].…”
Section: Introductionmentioning
confidence: 99%
“…8 Community pharmacies are a good potential site for identifying cardiovascular risk factors and improving disease detection, 9 including identifying people with hypertension, because of their accessibility and because many pharmacies provide free access to BP monitors. Pharmacists have been involved in successful community-based screening programmes developed to improve detection and treatment of hypertension, both in the UK and worldwide.…”
Section: Introductionmentioning
confidence: 99%